1940
DOI: 10.1085/jgp.24.1.105
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Stimulation of the Senses of Vision, Hearing, Taste, and Smell Upon the Sensibility of the Organs of Vision

Abstract: HISTORICALIt has long been known that the stimulation of one sense organ influences in some degree the sensitivity of the organs of another sense. But whether the influence is exerted upon the receptors or upon their central areas in the cortex has not been with certainty determined. This behavior of the nervous system may readily be inferred from its synaptical arrangement and intemunciatory constitution whereby all parts are susceptible of communication with each other. These ideas have thus been summsrized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1943
1943
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…The converse direction of effect ö odour 3 vision interaction ö has been much less investigated, although it has been pioneered early (Allen and Schwartz 1940). More recently, subtle interactions between olfaction and vision have been highlighted.…”
mentioning
confidence: 99%
“…The converse direction of effect ö odour 3 vision interaction ö has been much less investigated, although it has been pioneered early (Allen and Schwartz 1940). More recently, subtle interactions between olfaction and vision have been highlighted.…”
mentioning
confidence: 99%
“…Maruyama (1957Maruyama ( , 1959 found that this effect is dependent on the frequency and intensity of the auditory stimulus. Kravkov and subsequent researchers have found that sensitivity to green light increases as sound intensity increased, but that this effect is reversed for orange-red light (Allen and Schwartz, 1940;Kravkov, 1936Kravkov, , 1939Letourneau, 1972;Letourneau and Zeidel, 1971). Other studies have found inhibitory effects (Davis, 1966;Maloney and Welch, 1972) and that the effect is dependent on the temporal relationship between the stimuli in each modality (Broussard, Walker, and Roberts, 1952;Coleman and Krauskopf, 1956;Ince, 1968) or with no effect whatsoever (Symons, 1963).…”
Section: Interaction Of Audition and Visionmentioning
confidence: 97%
“…Or, in other words, does (or can) what we taste/smell capture and/or change, what we see? The most relevant evidence on the latter question, comes from research showing that olfactory cues can be used to draw people's visual attention to the congruent, or related, stimuli in a visual scene (e.g., see Chen, Zhou, Chen, He, & Zhou, 2013;Seigneuric, Durand, Jiang, Baudouin, & Schaal, 2010;Seo, Roidl, Müller, & Negoias, 2010; see also Allen & Schwartz, 1940, for early work on this topic). So, for example, both Seigneuric et al and Seo et al reported that olfactory stimuli tend to bias free-viewing behaviour (i.e., overt visual attention), such that participants are more likely to look at the object that is linked to (or associated with) the smell than they are when the odour is absent.…”
Section: Sensory Dominancementioning
confidence: 99%